Canine Bilateral Conjunctivo-Palpebral Dermoid: Description of Two Clinical Cases and Discussion of the Relevance of the Terminology. (23rd March 2015) - Balland, O.; Raymond, I.; Mathieson, I.; Isard, P. F.; Vidémont-Drevon, Emilie; Dulaurent, T.
Abstract : Two young dogs were presented for the evaluation of an abnormally haired appearance of both eyes since adoption. In one dog, the lesions were symmetrical and appeared as disorganized skin tissue located on the cutaneous aspect of the lateral portion of both lower eyelids, and continuing to the palpebral and the bulbar conjunctiva, thus forming continuous lesions. In the other dog, a similar lesion was present in the right eye (OD), but the lesion of the left eye (OS) was of discontinuous, disorganized skin tissue located midway on the lower eyelid and on the lateral bulbar conjunctiva. The lesions were surgically removed and routinely processed for histopathological analysis. Definitive diagnosis was conjunctivo-palpebral dermoids for each dog. Dermoids are usually considered to be choristoma (normal tissue in an abnormal location) when they are located on the ocular surface (cornea and/or conjunctiva) and as hamartoma when located on the palpebral skin. The lesion presentation in these two dogs reveals that names of "choristoma" alone or "hamartoma" alone are not accurate to depict the continuous, composite, conjunctivo-palpebral dermoids. These cases suggest that choristoma and hamartoma might develop subsequently from the same abnormal event during the embryonic development, which means that the lesion location might be the only difference between the two terms.